2019
DOI: 10.3390/cells8101159
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane-Induced Klf9/Prdx6 Axis Acts as a Molecular Switch to Control Redox Signaling and Determines Fate of Cells

Abstract: Sulforaphane (SFN), an activator of transcription factor Nrf2 (NFE2-related factor), modulates antioxidant defense by Nrf2-mediated regulation of antioxidant genes like Peroxiredoxin 6 (Prdx6) and affects cellular homeostasis. We previously observed that dose levels of SFN are crucial in determining life or death of lens epithelial cells (LECs). Herein, we demonstrated that higher doses of SFN (>6 μM) activated death signaling by overstimulation of Nrf2/ARE (antioxidant response element)-mediated Kruppel-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(100 citation statements)
references
References 123 publications
(219 reference statements)
5
95
0
Order By: Relevance
“…Klf9-mediated oxidative stress was evaluated in vivo using bleomycin-induced pulmonary fibrosis model mice, and Klf9-KO mice exhibited a decrease in 8-OHdG levels and fibrosis [88]. Chhunchha et al also reported an adverse effect of Klf9 in human lens epithelial cells treated with high-dose sulforaphane [89]. Low-dose sulforaphane induces peroxiredoxin-6 (Prdx6) gene expression via Nrf2 and ARE in its regulatory region; however, high-dose sulforaphane suppresses Prdx6 expression via Klf9 and the repressive Klf9 binding element (RKBE).…”
Section: Oxidative Stress Thresholding By Nrf2 and Klf9mentioning
confidence: 99%
See 2 more Smart Citations
“…Klf9-mediated oxidative stress was evaluated in vivo using bleomycin-induced pulmonary fibrosis model mice, and Klf9-KO mice exhibited a decrease in 8-OHdG levels and fibrosis [88]. Chhunchha et al also reported an adverse effect of Klf9 in human lens epithelial cells treated with high-dose sulforaphane [89]. Low-dose sulforaphane induces peroxiredoxin-6 (Prdx6) gene expression via Nrf2 and ARE in its regulatory region; however, high-dose sulforaphane suppresses Prdx6 expression via Klf9 and the repressive Klf9 binding element (RKBE).…”
Section: Oxidative Stress Thresholding By Nrf2 and Klf9mentioning
confidence: 99%
“…Low-dose sulforaphane induces peroxiredoxin-6 (Prdx6) gene expression via Nrf2 and ARE in its regulatory region; however, high-dose sulforaphane suppresses Prdx6 expression via Klf9 and the repressive Klf9 binding element (RKBE). These reports implicate Klf9 as a factor determining cell fate in response to the magnitude of oxidative stress, and Klf9 suppression/inhibition is a possible strategy to alleviate the side effects of Nrf2-activating interventions [89] (Figure 4).…”
Section: Oxidative Stress Thresholding By Nrf2 and Klf9mentioning
confidence: 99%
See 1 more Smart Citation
“…However, under conditions with an excessive level of ROS, the continuous activation of Nrf2 causes its accumulation in the nucleus and subsequent binding to the Kruppel-like factor 9 (Klf9) promoter. The upregulation of Klf9 transcription, which is a novel regulator of intracellular ROS, could then lead to increased levels of ROS and subsequent cell death [41,42]. Therefore, according to the studies, an excessive amount of oxidative stress is needed to activate the Klf9 transcription, which will be unlikely with a viral infection since the virus needs to keep oxidative stress at an optimal level to maintain viral metabolism without causing host cell death [43].…”
Section: Nrf2 Activation and Covid-19 Infectionmentioning
confidence: 99%
“…Therefore, we have summarized some studies on the protection of LECs under stress through Nrf2 pathways. The use of Nrf2 activators (such as SFN pretreatment [85]) or the overexpression of Nrf2 [86] can reduce DNA fracture; upregulate Nrf2, NQO1, HO-1, etc. [87]; and protect LECs from OS damage.…”
Section: Fuchs' Endothelial Corneal Dystrophy (Fecd)mentioning
confidence: 99%